Fukuyama at the Crossroads? - A Review Essay - Michael Peters (Social Work and Society, 2007)
Francis Fukuyama's book America at the Crossroads: Democracy, Power, and the Neoconservative Legacy , the latest from a prolific writer who as a neoconservative thinker has contributed many books on political and economic development, concerns American foreign policy since 9/11. It is a book that has a confessional tone when he traces his pedigree and how his views deviate from the outlook of his neoconservative friends"”Paul Wolfowitz, Albert Wohlstetter, Allan Bloom, and William Kristol. As he writes "˜unlike manu other neoconservatives, I was never persuaded of the rationale of the Iraq war' (p. x). He goes further "˜I have concluded that neoconservatism, as both a political symbol and a body of thought, has evolved into something that I can no longer support' (p.xi). By this he means insofar as neoconservatism has been irretrievably identified with the policies of the Bush administration, he thinks it has 'gone wrong' and he wants to outline a position he calls "˜realistic Wilsonianism' as the basis for a position not captured in the U.S. foreign policy debate that serves as an alternative means of the U.S. relating to the rest of the world. He omits from his biographical Preface the fact that he was active in the Project for the New American Century [1] starting in 1997 and also signed the organization's letter to President Clinton recommending the overthrow of Saddam Hussein and another calling for his overthrow in 2001.